Studies of genetic variability, quantitative and qualitative traits of Lilium cultivars (Lilium x hybrida) under shade net in North-West Himalayan region of India - Ajay Kumar Singh; Rakesh Kumar; Hitesh Kumar (Ornamental Horticulture, 2020)
An experiment was conducted to evaluate the performance of nine exotic lilium cultivars (Lilium x hybrida) for suitability for commercial cultivation in North Western hilly regions of Uttarakhand at Research Station and KVK, Lohaghat, GBPUA&T, Pantnagar, Champawat, Uttarakhand India. Bulbs of nine lilium hybrid cultivars viz., Acapulco (Pink), Sorbonne (White), Yelloween (Yellow), Tresor (Orange), Brindisi (Pink), Blackout (Red), Pavia (Yellow), Ercolano (White) and Samur (Pink) were selected as experimental material. There was significant difference in days taken for bud initiation among nine cultivars. It is evident from data that minimum days take for bud initiation in cultivar Blackout (43.80 days) followed by Tresor (45.40 days). The maximum number of flowers per plant reported in cultivars Acapulco (10.20) followed by Yelloween (8.20) and Sorbonne (7.80) which is at par with Blackout (7.40) and Pavia (7.20). Maximum vase life was recorded with Acapulco (12.4 days) followed by Sorbonne (11.80 days) which is at par with Yelloween (11.8 days) while Minimum vase life was recorded with Ercolano (8.40 days) and Tresor ( 8.40 days). Mean value was found maximum for flower stem length (87.29) and minimum mean value was exhibited by number of flowers per plant. Heritability value was found maximum for characters like days to flower bud opening followed by length of flower stalk and days taken to bud initiation.